Eksistensi BP4 Lampung Selatan sebagai Penasihat Perkawinan (Studi pada Perceraian Aparatur Sipil Negara Tenaga Medis) - Salsabila, Fairuz; Putriani, Rizki (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
As a marriage advisor, builder and guardian, BP4 has an important role in maintaining the integrity of the household. However, in reality BP4 has not carried out its roles and functions optimally. It can be seen from divorce cases which have become a common problem. This study purpose to find out why the existence of BP4 is disable to prevent divorce, especially the civil servant for medical personnel. This study used a qualitative descriptive method with a psychological approach. The results of this study indicate that the existence of BP4 is not well established. Even though it has been established several decades ago, in fact BP4 is still disable to prevent divorce. One of the reasons is because BP4 does not get material and non-material support from the government, so that in its movement BP4 has many limitations. Furthermore, the results of interviews and documentation related to divorce for medical personnel, shows that dishonest, lack of physical and spiritual support, quarrels and disputes, and not having children, are the background for medical personnel to divorce. Based on this explanation, it can be concluded that divorces in medical personnel are similar to divorces in general society. Its shows that divorce is not related to a profession.